New species and occurrence records of Japanese Solasteridae and Ganeriidae including a new species of Paralophaster from the North Pacific with an overview of Hyalinothrix - Mah, Christopher L.; Fujita, Toshihiko (Zootaxa, 2020)
Japanese waters contain a highly diverse echinoderm fauna including many undiscovered species, especially in deeper-water settings. Molecular phylogenetic data has shown a close relationship between three established families of asteroids, the Asterinidae, the Solasteridae and the Ganeriidae, which are three groups that are well-represented in the region. We present two undescribed species of solasterids, Lophaster cactorum n. sp. and Paralophaster gomo n. sp., the latter represents a genus which had previously been known primarily from Antarctic settings. New occurrence records of the tropical deep-sea Pacific solasterid Rhipidaster vannipes Sladen, 1889 has led to synonymy of Xenorias polyctenius Fisher, 1913. Three undescribed species of Hyalinothrix, Hyalinothrix diversus n. sp., Hyaliothrix enoki n. sp. and Hyalinothrix virtrispinum n. sp. are described. Nepanthia grangei McKnight, 2001 is transferred to Hyalinothrix. A new subfamily, the Hyalinothricinae is established within the Asterinidae, including Tarachaster and Seriaster, which was formerly assigned to the Solasteridae. Knightaster is reassigned to the Asterinidae from the Ganeriidae.